Successful Emergency Transcatheter Aortic Valve Replacement for Severe Aortic Regurgitation in Takayasu’s Arteritis - Takanori Kawamoto, MD, PhD; Hisao Otsuki, MD, PhD; Masataka Hirota, MD; Masafumi Yoshikawa, MD, PhD; Eiji Shibahashi, MD, PhD; Yusuke Inagaki, MD, PhD; Tomohito Kogure, MD, PhD; Satoru Domoto, MD, PhD; Hiroshi Ninami, MD, PhD; Junichi Yamaguchi, MD, PhD (JACC: Case Reports)
Background: Takayasu’s arteritis (TA) is a rare inflammatory disease that often causes aortic regurgitation (AR). However, severe arterial degeneration sometimes complicates surgical intervention. Case summary: A 62-year-old woman with TA developed refractory heart failure due to severe noncalcified AR. Surgery was not feasible because of the extreme calcification of the aorta. Emergency transcatheter aortic valve replacement (TAVR) using a Sapien 3 Ultra RESILIA valve (Edwards Lifesciences) was performed. Subsequently, the heart failure improved substantially. Discussion: Severe arterial degeneration makes surgical intervention difficult for TA. When performing TAVR for noncalcified AR, careful selection of the prosthetic valve and deployment technique is crucial. Take-Home Message: A meticulous strategy is needed to safely perform TAVR with the currently available off-label prosthetic valves for cases of TA complicated by noncalcified AR that are difficult to manage with open-heart surgery.